Labor law vs. Cooperative law Analysis of public policies and rights found What prevails? - Gaudio, Ronaldo; Baiocchi, Enzo (Cooperativismo & Desarrollo, 2019)
This work aims to raise awareness and generate discussion on a topic that has emerged in Puerto Rico andpossibly other countries in Latin America and the Caribbean, although such a debate is not known or we havebeen able to identify it beyond the seas, including some discussion on the effects that could have in the different public policies approved by the National Governments. This debate because of its relationship with the working class and the cooperative class has the potential to provoke confrontations, intellectual and doctrinal and impact theories and positions on autonomy and independence of cooperativism, which imposes the obligation to rethink the issue and raise it to public discussion including the need to improve cooperative education and more rigorously in people who are forced to interpret the current legislation and adopt determinations on their reach more when such public policy is born of social legislation.
Keywords: Competition Law; Cooperative Law; cooperative cooperation; health cooperatives; regulation; development